Implementasi Algoritma Wagner-Within pada Manajemen Inventori di PT X - Katias, Puspandam; Affandi, Achmad (Jurnal Bisnis dan Keuangan, 2018)
The increasing competition in the manufacturing industry caused increasing inconsumer demand of the quality and quantity of a good product. Therefore, manufacturing companies must have reliable services, policies and product qualities to satisfy its customers. So it needs to be supported by efficient production system and inventory system. To able to create an efficient production system then need a good raw material inventory planning. This research aims to compere how efficiently in planning raw materials inventory between Wagner-Within Algorithm with the actual concept that applied to PT X, Sidoarjo. The methodology of this research is qualitative descriptive research. The findings this research is engaged in packaging (woven bag and jumbo bag) with main raw materials such as plastic ore and supporting material in inner, thread, additive, and pigment. Based on the result of the analysis is known that the actual concept of the company gives the total inventory cost IDR 3.151.000.000 with the frequency of ordering 12 times while WagnerWithin Algorithm method provides a more efficient total inventory cost of Rp. 2.685.821.101 with8 times the frequency of ordering and can savings of 14.8% of total raw material inventory cost.